Mechanism of H2-O2 reaction in supercritical water. (1st May 2022) - Su, Di; Bei, Lijing; Zhang, Jiawei; Jin, Hui; Ge, Zhiwei; Guo, Liejin
Highlights: Experiment with equivalence ratio ranging from 3.5 to 7.2 indicates the global reaction rate is independent of O2 . Reduced mechanisms are derived by applying quasi-steady-state approximation to analyze reaction details. Special role of H + O2  + M → HO2  + M is responsible for concurrence of independences of its reaction coefficient, O2, and H. HO2 is a reliable marker of reactive intensity due to small activation energy of reaction HO2  + HO2  → H2 O2  + O2 and a thermal system. Abstract: H2 -O2 reaction in supercritical water has been widely studied due to its promising application in industry. The global rate of this reaction was found independent of O2 with equivalence ratio ranging from 0.042 to 4.1 in the literature. Aim of current study is to examine intermediates interaction responsible for properties of the O2 independence and others. The study involves experiment re-examining the oxygen independence phenomenon and simulation centering on reduced mechanisms derived by quasi-steady-state approximation. The experiment with equivalence ratio ranging from 3.5 to 7.2 produces similar temperature increases, signifying a global reaction rate independent of oxygen. The phenomenon of oxygen independence was then inspected by a three-step reduced mechanism and is attributed to a special role of H + O2  + M → HO2  + M. This particular reaction dominating H and O2 consumption with a fast rate is responsible for the concurrence of independences of its reaction coefficient, H, and O2 to global reaction rate. Another property that HO2 quantity indicates reactive intensity was investigated by a two-step reduced mechanism and is credited to a small activation energy of reaction HO2  + HO2  → H2 O2  + O2 and a thermal system.